PHYSICAL ACTIVITY AND VITAMIN D LEVEL IN ASTHMA AND NON-ASTHMA AKTIVITAS FISIK DAN KADAR VITAMIN D PADA PASIEN ASMA DAN NON-ASMA - Lorensia, Amelia; Suryadinata, Rivan Virlando; Saputra, Rifaldi (Jurnal Farmasi Indonesia, 2019)
Worsen asthma symptoms is associated with low vitamin D levels that increases asthma attacks risk. Physical activity is one factor that affects vitamin D levels in the blood. This study aimed to identify relationship physical activities effects with vitamin d levels on asthma and non-asthma patients. The study was conducted in March-June 2018. The subjects were asthma patients and non-asthma adults and didn’t have other comorbidities. Data analysis used pearson test to determine physical activity effect with vitamin D levels. There were significant differences in vitamin D levels (P <0.000) and physical activity (P <0.000) in asthma and non asthma respondents. The results of the correlation test between vitamin D levels and physical activity in Approximate Significance value was 0.965, which means there were very strong relationships between vitamin levels and physical activity on the respondents of asthma and non asthma. So, the asthma patients with sufficient physical activity will have normal vitamin D levels to improve control of asthma symptoms. Worsen asthma symptoms is associated with low vitamin D levels that increases asthma attacks risk. Physical activity is one factor that affects vitamin D levels in the blood. This study aimed to identify relationship physical activities effects with vitamin d levels on asthma and non-asthma patients. The study was conducted in March-June 2018. The subjects were asthma patients and non-asthma adults and didn’t have other comorbidities. Data analysis used pearson test to determine physical activity effect with vitamin D levels. There were significant differences in vitamin D levels (P <0.000) and physical activity (P <0.000) in asthma and non asthma respondents. The results of the correlation test between vitamin D levels and physical activity in Approximate Significance value was 0.965, which means there were very strong relationships between vitamin levels and physical activity on the respondents of asthma and non asthma. So, the asthma patients with sufficient physical activity will have normal vitamin D levels to improve control of asthma symptoms.